PENGARUH LITERASI TIK DAN SOFT SKILLS TERHADAP KESIAPAN KERJA SISWA SMK MELALUI MEDIASI SELF REGULATED LEARNING DI KABUPATEN PANGKEP - Alifyaramadani Hidayah; Nurlaela; Hamzah Nur (UNM Journal of Technology and Vocational, 2026)
This study aims to examine and empirically analyze the influence of ICT literacy and soft skills on vocational high school students’ work readiness, with self-regulated learning as a mediating variable in Pangkep Regency. The research employed a quantitative approach with an ex post facto design, focusing on testing the relationships among variables based on questionnaire data. The population consisted of 624 students, while the sample included 244 eleventh-grade students selected through cluster sampling based on sub-district areas, followed by proportional random sampling from each school. Data analysis was conducted using Structural Equation Modeling with Analysis of Moment Structures. The results indicate that ICT literacy has a positive and significant effect on work readiness and a stronger effect on self-regulated learning. Soft skills also show a positive and significant effect on work readiness and self-regulated learning. Furthermore, self-regulated learning has a positive and significant effect on work readiness. In the mediation analysis, self-regulated learning significantly mediates the effect of ICT literacy on work readiness as well as the effect of soft skills on work readiness. These results indicate that students’ work readiness is shaped not only by ICT literacy and soft skills but also through the role of self-regulated learning as a mediating factor.